Effect of Construction Labour Group Composition on Optimal Field Labour’s Productivity in Malang- East Java - Tjaturono, Tjaturono (MEDIA KOMUNIKASI TEKNIK SIPIL, 2010)
One of the main factor which determines the labour productivity is the labour group composition. In Indonesia, the cost estimate of construction labour uses the labour groups of the productivities in Indonesian National Standard 2002 (SNI 2002) and itsmodofocation. However, using these productivities is not efficient and effective. This paper intens to detemnine the ideal labour group composition, the equivalent coefficient and the difference between the actual productivities and the productivities of SNI 2002. The research methodology used consist of field observation and interview with 240 labour groups of various compositions in the construction of middle-class houses in Malang, East Java. The data were processed by descriptive statistics and statistical test for mean differences. The result of this research shows that the ideal composition for floor tile laying, sawn form work, and concrete pouring are: 1 tiler: 2 labours, and 1 mason:4 labours respectively, the equivalent coefficients for various labour group compositions are obtained. The differences between the field productivities and the productivities of SNI 2002 for tile laying, sawn form work and concrete pouring are 286%, 114.8%, and 18% respectively. Keywords : Labour group composition, SNI 2002, field labour’s productivity, middle-class housing.   Abstrak   Salah satu faktor utama yang menentukan produktivitas tenaga kerja adalah komposisi kelompok kerja. Di Indonesia, estimasi biaya tenaga kerja konstruksi menggunakan komposisi kelompok kerja produktivitas Standar Nasional Indonesia (SNI) 2002 dan modifikasinya. Namun penggunaan produktivitas ini tidak efisien dan efektif. Tulisan ini bertujuan untuk menentukan komposisi kelompok kerja yang ideal, koefisien penyetaraan serta perbedaan produktivitas actual terhadap produktivitas SNI 2002. Metode penelitian yang dipakai adalah observasi lapangan dan wawancara terhadap 240 komposisi kelompok kerja pada pembangunan rumah menengah di Malang Jawa Timur. Data diolah secara statistic deskriptif dan statistical test for a mean differences. Dari hasil penelitian ini diperoleh komposisi kelompok kerja yang ideal untuk pasang tegel lantai, belisting dan pengecoran beton adalah: 1 tukang tegel: 2 pekerja, 1 tukang kayu:1 ½ pekerja dan 1 tukang batu: 4 pekerja. Diperoleh juga koefisien penyetaraan untuk berbagai komposisi kelompok kerja. Serta perbedaan produktivitas lapangan terhadap SNI 2002 untuk pekerjaan pasang tegel, belisting dan pengecoran beton sebesar 286%, 114,8% dan 18%. Kata-kata Kunci : Komposisi kelompok kerja, SNI 2002, Produktivitas tenaga kerja lapangan, Rumah menengah.